Consensus Guidelines for Advancing Coral Holobiont Genome and Specimen Voucher Deposition - Christian R. Voolstra; Kate M. Quigley; Sarah W. Davies; John Everett Parkinson; Raquel S. Peixoto; Manuel Aranda; Andrew C. Baker; Adam R. Barno; Daniel J. Barshis; Francesca Benzoni; Victor Bonito; David G. Bourne; et al. (Frontiers in Marine Science, 2021)
Coral research is being ushered into the genomic era. To fully capitalize on the potential discoveries from this genomic revolution, the rapidly increasing number of high-quality genomes requires effective pairing with rigorous taxonomic characterizations of specimens and the contextualization of their ecological relevance. However, to date there is no formal framework that genomicists, taxonomists, and coral scientists can collectively use to systematically acquire and link these data. Spurred by the recently announced “Coral symbiosis sensitivity to environmental change hub” under the “Aquatic Symbiosis Genomics Project” - a collaboration between the Wellcome Sanger Institute and the Gordon and Betty Moore Foundation to generate gold-standard genome sequences for coral animal hosts and their associated Symbiodiniaceae microalgae (among the sequencing of many other symbiotic aquatic species) - we outline consensus guidelines to reconcile different types of data. The metaorganism nature of the coral holobiont provides a particular challenge in this context and is a key factor to consider for developing a framework to consolidate genomic, taxonomic, and ecological (meta)data. Ideally, genomic data should be accompanied by taxonomic references, i.e., skeletal vouchers as formal morphological references for corals and strain specimens in the case of microalgal and bacterial symbionts (cultured isolates). However, exhaustive taxonomic characterization of all coral holobiont member species is currently not feasible simply because we do not have a comprehensive understanding of all the organisms that constitute the coral holobiont. Nevertheless, guidelines on minimal, recommended, and ideal-case descriptions for the major coral holobiont constituents (coral animal, Symbiodiniaceae microalgae, and prokaryotes) will undoubtedly help in future referencing and will facilitate comparative studies. We hope that the guidelines outlined here, which we will adhere to as part of the Aquatic Symbiosis Genomics Project sub-hub focused on coral symbioses, will be useful to a broader community and their implementation will facilitate cross- and meta-data comparisons and analyses.